Tratamento interdisciplinar em adolescentes obesos com esteatose hepática não alcoólica: papel dos neuropeptídeos e adipocinas pró e anti-inflamatórias - Ganen, Aline de Piano [UNIFESP] (2011)
BACKGROUND: The complexity physiophatology in the Non Alcoholic Fatty Liver Disease (NAFLD) involves interplay between adipokines and neuroendocrine regulation of energy balance, including the role of Neuropeptide Y/Agouti Related Protein system. AIM: establishing the relationship between Neuropeptide Y/Agouti Related Protein (NPY/AgRP) ratio and adiponectinemia, as well as to assess the influence of orexigenic neuropeptides in the nutritional aspects of NAFLD obese adolescents submitted to a long-term interdisciplinary approach. METHODS: A group of post-pubescent obese adolescents were recruited and included in the interdisciplinary intervention. The group was analyzed according to the presence or ausence of NAFLD by ultrassonography (US). Blood samples were collected to measure glycemia, hepatic transaminases and lipid profile, insulin resistance and sensitivity. Adiponectin, NPY and AgRP concentrations were measured by ELISA and the measurement of visceral ans subcutaneous fat by US. Food intake was measured using 3-day diet records. RESULTS: It was observed at baseline that important clinical parameters including body weight, BMI, visceral fat, HOMA-IR, QUICKI, triglycerides, VLDL-cholesterol and hepatic transaminases were more altered in NAFLD patients. After the intervention, these parameters, total energy and macronutrient intake were reduced significantly in both groups. The most important finding was the positive correlation between AgRP with visceral fat in all patients, and negative correlation between NPY/AgRP with adiponectin only in NAFLD obese adolescents. Analyzing the influence of the diet in the orexigenic neuropeptides, only the NAFLD patients presented a positive correlation between the saturated fatty acids intake and the orexigenic neuropeptides (NPY and AgRP); and carbohydrate with NPY. Indeed, it was observed a positive correlation between energy intake, lipid (%) and saturated fatty acids with visceral fat accumulation. CONCLUSION: NAFLD patients presented more altered clinical parameters than non-NAFLD, including the negative correlation between adiponectin and NPY/AgRP. These results suggested that NAFLD obese adolescents presented an altered inflammatory profile that can influence the neuroendocrine regulation of energy balance suggesting and additional impairment in the weigth loss therapy. Moreover, our findings showed an important influence of diet composition in the orexigenic system, being essential consider that the excessive saturated fatty acids intake could be a determinant factor to increase nonalcoholic fatty liver disease.